Clinical characteristics and treatment requirements of children with autosomal recessive pseudohypoaldosteronism. Issue 5 (May 2021) - Bandhakavi, Meena; Wanaguru, Amy; Ayuk, Loveline; Kirk, Jeremy M; Barrett, Timothy G; Kershaw, Melanie; Högler, Wolfgang; Shaw, Nicholas J
Abstract : Introduction: Autosomal recessive forms of pseudohypoaldosteronism are caused by genetic defects in the epithelial sodium channel. Little is known about the long-term outcome and medication needs during childhood and adolescence. Objective: This study reports a single-centre experience of children affected with this ultra-rare condition over a 37-year period. Methods: We report the clinical presentation, growth, neuro-development, associated conditions, mortality and medication dosing and administration for 12 affected children from eight families. Results: All children were presented within the first 2 weeks of life with life-threatening, severe hyperkalaemia and hyponatraemia. All parents were consanguineous and of South Asian, Middle Eastern or African ethnic origin. Eight children had homozygous mutations in the SCNN1A and SCNN1G genes, encoding the epithelial sodium channel subunits alpha and gamma, respectively, including one novel mutation. Three children died (25%) and two (16%) had severe neurological impairment post-cardiac arrest secondary to hyperkalaemia. One affected female had a successful pregnancy at the age of 28 years. Conclusion: Despite high mortality and morbidity in this condition, survival with normal physical and neurological outcome is possible, justifying intensive management to prevent electrolyte imbalance.